MURALDEFINISI DAN SEJARAH PERKEMBANGANNYA - Isnanta, Satriana Didiek (Institut Seni Indoensia Surakarta, 2016)
The presence of the mural in the development of human civilization have been found long ago. Murals or painted walls has existed since prehistoric times that the site is in caves. Mural always follow human civilization, including modern human civilization now. In modern civilization, mural functions continue to evolve, as well as wall hangings, mural also serves as a medium for propaganda, protest against the authorities, the existence of self-identity politics and group, artistic expression, and as an advertising medium. In the context of contemporary art, murals entry in the genre of public art (publicart) and street art (street art), which in conjunction with other types of street art like graffiti. Problems arise when, performers (creator), public (apresiator) and government (stakeholders-holder regulation) do not understand the definition and historical development of this mural, so it can not distinguish between murals and graffiti. This gives rise to misunderstanding among them. On the one hand, considers that the expression of art, on the other hand considers murals make the city dirty. Therefore, it is important to make a study of literature relating to the definition and development mural to be a reference material for mural artists and government policy makers. Kepustakan research method is using a discourse analysis of data taken from various books, scientific articles, photo and video documentation, catalogs and media coverage.Keywords: murals, public art, contemporary art.